3D printing of fully recyclable continuous fiber self-reinforced composites utilizing supercooled polymer melts. (June 2023) - Zhang, Manyu; Tian, Xiaoyong; Cao, Hanjie; Liu, Tengfei; Akmal Zia, Ali; Li, Dichen
Graphical abstract: Abstract: A 3D printing approach for fully recyclable continuous fiber self-reinforced composites (CFSRCs) utilizing supercooled polymer melts was proposed. Continuous autologous fibers were added to the supercooled melt zone below the polymer matrix melting temperature avoiding fiber melting which successfully enlarged the processing temperature window. Through controlled supercooled melt conditions and heat transfer simulation, the supercooled melting temperature gradient control strategy for 3D printing CFSRCs were established. The processing temperature window enlarged from 2℃ to 30℃. Then the intrinsic connection among the printing temperature, crystallization behavior and mechanical properties of 3D printed CFSRCs were analysed. Furthermore, the interlaminar shear strength and transverse tensile property of CFSRCs were excellent than carbon fiber reinforced composites. Lastly, confirmation of the full recyclability of self-reinforced composites by mechanical recycling without mechanical property loss compared with virgin matrix. Fully recyclable CFSRCs based on 3D printing potentially establish a closed-loop recycling strategy for space applications.